2022
DOI: 10.1111/jcmm.17626
|View full text |Cite
|
Sign up to set email alerts
|

Bacteroides plebeius improves muscle wasting in chronic kidney disease by modulating the gut‐renal muscle axis

Abstract: Chronic kidney disease (CKD) affects approximately 10% of the global population. Muscle atrophy occurs in patients with almost all types of CKD, and the gut microbiome is closely related to protein consumption during chronic renal failure (CRF). This study investigated the effects of Bacteroides plebeius on protein energy consumption in rats with CKD, and our results suggest that Bacteroides plebeius may combat muscle atrophy through the Mystn/ActRIIB/SMAD2 pathway. A total of 5/6 Nx rats were used as a model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…36 Moreover, Bacteroides plebeius has been reported to inhibit chronic kidney disease-induced muscle atrophy in animal models. 37 These findings may suggest a beneficial association between the Bacteroides genus and sarcopenia and skeletal muscle phenotypes. On the other hand, a previous study analyzing species-level gut microbiota reported that the relative abundance of Bacteroides fluxus was positively associated with the severity of sarcopenia.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…36 Moreover, Bacteroides plebeius has been reported to inhibit chronic kidney disease-induced muscle atrophy in animal models. 37 These findings may suggest a beneficial association between the Bacteroides genus and sarcopenia and skeletal muscle phenotypes. On the other hand, a previous study analyzing species-level gut microbiota reported that the relative abundance of Bacteroides fluxus was positively associated with the severity of sarcopenia.…”
Section: Discussionmentioning
confidence: 90%
“…Additionally, a study of Japanese long‐distance runners found an association between Bacteroides uniformis and endurance exercise performance, with α‐cyclodextrin supplementation increasing B. uniformis and improving endurance exercise performance 36 . Moreover, Bacteroides plebeius has been reported to inhibit chronic kidney disease–induced muscle atrophy in animal models 37 . These findings may suggest a beneficial association between the Bacteroides genus and sarcopenia and skeletal muscle phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…While B. thetaiotaomicron , B. fragilis BOB25, B. fragilis JIM10 and B. intestinalis have been extensively studied, the importance of B. plebeius in maintaining gastrointestinal homeostasis has not been previously assessed. Today it is known that B. plebeius can enhance the barrier function of the intestinal mucosa and modify the intestinal microbiome ( Pei et al, 2022 ). Indole also has a significant number of reported biological properties beneficial to the human.…”
Section: Discussionmentioning
confidence: 99%
“… 34 , 35 Pei et al .’s research discovered that Bacteroides could also improve the barrier function of the intestinal mucosa and inhibit the Mystn/ActRIIB/SMAD2 pathway to prevent muscle atrophy. 36 In general, Bacteroides can affect muscle function and mass by improving intestinal absorption and energy metabolism. A study transplanted the feces of HF (high-function) and LF (low-function) elderly separately into germ-free mice, and the grip strength of HF-colonized mice increased after a 1-month follow-up, which suggested that these gut microbiota had a beneficial role in maintaining muscle strength in the elderly over 65 years old.…”
Section: Discussionmentioning
confidence: 99%